Dialectical materiality and collective habitat: ANCESTRA, architecture in conflict territories - Andrade, Jhonatan (Artes: Architecture, Technology and Sustainability, 2026)
This article analyzes ANCESTRA’s practice from its own territory: Durán, Ecuador, one of the country’s most conflictive and vulnerable urban contexts. Its objective is to demonstrate that the studio formulates a critical architecture not from formal abstraction, but from the reading of concrete material contradictions: territorial violence, fragmentation of the social fabric, infrastructural precariousness, unstable popular economies, and the lack of governmental support systems capable of repairing collective life. The theoretical framework brings together Latin American debates on unequal urbanization, the social production of space, and habitat, alongside references to Ecuadorian and regional practices that have worked through local resources, community organization, and open design systems. The methodology consists of a qualitative and interpretive analysis of three ANCESTRA case studies: La Carpa, Atacapi Community Center, and La Colmena, the latter developed in collaboration with the Babahoyo-based studio Natura Futura. The results show that the studio translates territorial conflicts into spatial, technical, and programmatic decisions capable of dignifying everyday practices and reconstructing the supports of daily life. The article concludes that ANCESTRA develops an architecture of material and social repair, grounded in dialectical materiality and in the need to intervene critically in territories marked by violence and inequality.